Penggunaan Media Pembelajaran dengan Benda Konkret untuk Meningkatkan Kemampuan Berhitung pada Peserta Didik Kelas II - Jahyus, Muhammad Ryan; Dzulqadri, Abrar; Febrian, Deni; Febrian, Febrian (Lembaga Yasin AlSys, 2023)
Learning outcomes are described as written statements of what a learner is expected to know, understand and/or be able to do at the end of a period of learning